Studies on certain haematological and biochemical constituents in cows with retained fetal membranes - RAY, S K H; DASH, H D; MOHANTY, D N; DAS, S; BISOI, P C; BARIK, A K (The Indian Journal of Animal Reproduction, 2023)
Ten cows with retention of foetal membrane (RFM) and six cows delivering normally were included in the presentinvestigation. Blood samples were subjected for estimation of certain haematological and biochemical constituents. The totalleucocytic count as well as eosinophil, basophil and monocyte percentage did not vary significantly between cows with RFM andnormal cows. Neutrophil count in RFM cases was significantly lower (P < 0.01 ), whereas lymphocyte percent in RFM wassignificantly higher (P < 0.0 I) than the values for normally delivered cows. The serum calcium, inorganic phosphorous, ALT_ andAST concentration in RFM cases did not differ significantly with normal parturient animals. On the contrary, the ALP activitieswere significantly higher (P < 0.01) in cows with retained fetal membrane (35.38± 1.69 IU/L) in comparison to normal cows(25.73±1.79 IU/L).
Keywords: RFM; TLC; biochemical, haematology; AST; ALT